(untitled) (UNIZIK Journal of Educational Management and Policy, 2024)
The study which aimed at determining the relationship between human resource planning and accreditation outcome in tertiary institution in Anambra State, Nigeria, adopted a co-relational study design. The population of the study stood at 320 respondents which comprised all heads of academic departments in tertiary institutions in Anambra State. A sample size of 135 heads of departments that carried out accreditation in at least one programme in the year 2021, 2022 and 2023 were selected for the study. The researcher used structured questionnaire titled Human Resource Planning Questionnaire (HRPQ), with eleven items. The face validity of the questionnaires was determined by three experts. The internal consistency of the instrument was determined using Cronbach’s Alpha reliability coefficient, of which 0.95 was obtained. The researcher together with 18 research assistants that lectures in the various institutions administered the instruments directly to the respondents. The data collected were analyzed using Pearson’s Product Moment Correlation Coefficient to answer the research question and multinomial logistic regression to test the null hypothesis at 0.05 level of significance. The decision to reject or fail to reject the hypothesis was based on probability value (p-value). Where the p-value was less than the stipulated level of significance (0.05), the null hypothesis was rejected, whereas the null hypothesis was not rejected where the calculated p-value is greater than the stipulated level of significance (0.05). The analysis was done using Statistical Package for Social Science (SPSS) version 21. The findings of the study show that there was negligible positive relationship between human resource planning and accreditation outcome in tertiary institutions in Anambra state. It was therefore concluded that there was non-significant relationship between human resource planning and accreditation outcome in tertiary institutions in Anambra state.Among the recommendation is that the federal, state and stakeholders should ensure that well qualified staff as stipulated in the accrediting agency’s guidelines be to adapt to changes in school environment and acquire the necessary knowledge for successful accreditation outcome.